Rationale, methods, and progress of the ArthroCaP Study: A prospective cohort study exploring the associations between chronic postsurgical pain and postoperative cognitive dysfunction after elective knee or hip arthroplasty. Issue 4 (22nd December 2022) - Khaled, Maram; Kuber, Jocelyn; Ferber, Mary; Sritharan, Praveen; Levy, Yarden; Becker, Suzanna; Fahnestock, Margaret; Griffin, Meridith; Madden, Kim; Shanthanna, Harsha; Marcucci, Maura
ABSTRACT: Background: Chronic postsurgical pain (CPSP) may increase the risk of postoperative cognitive dysfunction (POCD) directly or by negatively impacting mobility. A comprehensive measure of satisfaction with surgery that accounts for ability to perform activities might be even more strongly associated with POCD. There might be complex mechanisms underlying the interplays between postoperative pain and cognition. Aims: The primary objective is to explore whether CPSP at 6 months is associated with POCD (≥2-point decline in the Montreal Cognitive Assessment [MoCA] compared to preoperative) at 12 months. Secondary objectives are to explore the association between satisfaction with surgery and POCD, the role of pain medications (opioids) in the association between CPSP and POCD, the role of patient preoccupation/optimism and coping in determining the effect of pain on cognition, and the hypothesis of neurogenesis interference as an underlying mechanism. Methods: We will prospectively recruit ≥100 patients ≥50 years old undergoing elective total knee/hip arthroplasty. Sociodemographic characteristics, comorbidities, frailty, pain, and pain medications will be assessed preoperatively. The Somatic Preoccupation and Coping questionnaire will be administered preoperatively and 4 to 6 weeks postoperative. Pain and the Self-Administered Patient Satisfaction Scale will be measured at 3 and 6 months. MoCA and neuropsychological tests will be administered at baseline, 4 to 6 weeks, and 6 and 12 months. Blood will be longitudinally collected for biomarker analysis. Progress: Forty-six participants have been enrolled in the study so far. Conclusion: ArthroCaP will provide preliminary data on the association of CPSP and patient satisfaction with POCD and underlying mechanisms. It will inform larger confirmatory and interventional studies to enhance the benefits of surgery.